2018
DOI: 10.1111/ijn.12624
|View full text |Cite
|
Sign up to set email alerts
|

Promoting active ageing in older people with mental disorders living in the community: An integrative review

Abstract: Of concern is that health professionals focus on the physical health of older people while mental health issues are overlooked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Population aging is a public health success story, but at the same time it represents the challenge of maintaining the quality of life, functional capacity, and social participation of older adults [4]. In fact, there is an increasing incidence of mental disorders in the elderly, with depression and anxiety being the most commonly diagnosed mental disorders [5,6] may suffer from depression, with the prevalence increasing with age [7,8]. Depression is commonly treated with antidepressants in primary care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population aging is a public health success story, but at the same time it represents the challenge of maintaining the quality of life, functional capacity, and social participation of older adults [4]. In fact, there is an increasing incidence of mental disorders in the elderly, with depression and anxiety being the most commonly diagnosed mental disorders [5,6] may suffer from depression, with the prevalence increasing with age [7,8]. Depression is commonly treated with antidepressants in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is important to evaluate the association between PA levels and anxiety and depression, because these aspects can slow down the symptoms associated with the prevalence of chronic degenerative diseases [6]. Although there are many studies about the benefits of PA in mental health in older people [5,6,9,16,17], to the best of our knowledge, there are no known studies that have been conducted on pre-elderly people (a stage that ranges from 50 to 64 years according to several authors [30][31][32]) that relates mental health to levels of PA and the consumption of medications. Our hypothesis is that pre-elderly people who do moderate or intense PA have better mental health (suffer fewer problems of depression and anxiety), less consumption of medications and have a better state of health than sedentary people.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, older people experiencing mental disorders were not encouraged to participate in health promotion activities which were managed by Thai primary care units . The findings of a recent integrative review also indicated that there is an urgent need to provide evidence about the best ways for healthcare professionals to promote active ageing in older people with mental disorders living in rural areas . Furthermore, instruments examining how older people in this group have been engaged in active ageing, and examining what factors influence promoting active ageing in this group, have not yet been established …”
Section: Introductionmentioning
confidence: 99%
“…6 The findings of a recent integrative review also indicated that there is an urgent need to provide evidence about the best ways for healthcare professionals to promote active ageing in older people with mental disorders living in rural areas. 7 Furthermore, instruments examining how older people in this group have been engaged in active ageing, and examining what factors influence promoting active ageing in this group, have not yet been established. 7 In a previous study, we developed and tested preliminary results of a new instrument; the 'Promoting Active Ageing in Older People with Mental Disorders Scale' (PAA-MD), which was the first phase of a study involving the scale development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation